High‐risk pregnancy in a patient with pulmonary arterial hypertension due to congenital heart disease (PAH‐CHD) with temporary shunt inversion and deoxygenation. (1st March 2019) - Hohmann, Christopher; Dumitrescu, Daniel; Gerhardt, Felix; Kramer, Tilmann; Rosenkranz, Stephan; Huntgeburth, Michael
Abstract : Atrial septal defect (ASD) is one of the most frequent congenital heart diseases (CHD). Up to 10% of adults with an ASD develop pulmonary arterial hypertension (PAH, PAH‐CHD) in their lifetime. Despite improved therapy options, gravidity remains a substantial risk for both maternal and neonatal mortality in PAH‐CHD patients. In our patient, gravidity remained uncomplicated until week 32, under specific monotherapy with tadalafil, before onset of dyspnea and markedly increase of systolic pulmonary arterial pressure (PAP) was observed in echocardiography. Urgent Caesarian delivery was performed without any complications and a healthy baby was born. However, immediately afterwards, the patient desaturated (SpO2 65%, PaO2 37 mmHg) due to a shunt inversion with now right‐to‐left shunt through the residual ASD. She was admitted to our intensive care unit and specific PH therapy was escalated to a triple combination of tadalafil, ambrisentan, and iloprost. Hereafter, in a slow process of approximately three weeks, the patient's condition improved to baseline. This rare case of a young woman with high‐risk pregnancy in PAH‐CHD highlights the hemodynamic changes and treatment options during pregnancy in these patients and emphasizes the urgency of a close monitoring at specialized GUCH/PAH centers with experience in managing PAH under these circumstances.